2018
DOI: 10.1080/10942912.2018.1448994
|View full text |Cite
|
Sign up to set email alerts
|

Anticarcinogenecity of microbiota and probiotics in breast cancer

Abstract: Breast cancer is one of the most important causes of cancer related morbidity and mortality in the world. Along with genetic, environmental factors also play a multifaceted role in the development of disease. Breast contains several bacterial species performing specialized functions. Probiotics, as functional food, play pivotal role against breast cancer development in vivo and in vitro. Current review summarized all the available data related to diet, probiotics, and their association with breast cancer risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 103 publications
(115 reference statements)
0
16
0
2
Order By: Relevance
“…The antitumor/proliferative effect of Bifidobacterium spp. against breast cancer was also observed in vitro and in vivo 28 , 29 , indicating the loss of tumor-suppressor-like Bifidobacterium spp. in premenopausal breast cancer patients.…”
Section: Discussionmentioning
confidence: 87%
“…The antitumor/proliferative effect of Bifidobacterium spp. against breast cancer was also observed in vitro and in vivo 28 , 29 , indicating the loss of tumor-suppressor-like Bifidobacterium spp. in premenopausal breast cancer patients.…”
Section: Discussionmentioning
confidence: 87%
“…Moreover, probiotic bacteria can shift Th1 immune responses in infectious and cancer models. Also, the function of innate immune cells, including macrophages, dendritic cells, and natural killer cells is potentiated through these probiotic bacteria which in turn could stimulate adaptive immunity and consequently inhibition of the tumor growth [13,14]. In the present study, anticancer properties of Lactobacillus acidophilus and Bifidobacterium bifidum as two probiotic bacteria were evaluated on HT-29 and MCF7 cancer cell lines.…”
Section: Discussionmentioning
confidence: 95%
“…Flow cytometry with Annexin V–PI staining was used to confirm that CCS2 caused apoptosis in a concentration-dependent manner ( Figure 6 ). Studies have proven that the cell-free supernatant of Lacticaseibacillus brevis prevents proliferation and promotes apoptosis in breast cancer ( Malik et al, 2018 ). In another study, found that Lacticaseibacillus casei SR1, SR2, and Lacticaseibacillus paracasei SR4 act against cervical cancer cells via the intrinsic mitochondrial apoptotic pathway inducing apoptosis ( Riaz Rajoka et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%